Sociology of environment - Pawar, S. N.; Patil, R. B. (Rawat Publications, 1998)
Papers presented at the UGC-sponsored National Seminar on Society and Environment: Interface and Tensions, organized by and held at Department of Sociology, Shivaji University, Kolhapur, on March 27-29, 1995.